Educational Administration and its Role in Shaping Students' Attitudes Towards a Career in Teaching After Graduation at the Faculty of Education, Al-Zaytuna University (A Field Study) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the importance of educational administration in shaping students' attitudes towards working as teachers after graduation at the Faculty of Education in Tarhuna. The descriptive-analytical method was used, and the study sample consisted of 93 male and female students, selected using a comprehensive survey method. The results showed a positive attitude among the sample towards the importance of educational administration in shaping their attitudes towards working as teachers after graduation. This was attributed to the organization and implementation of lectures and educational courses aimed at enhancing the skills of graduating students and supporting the status of the teaching profession. The results also indicated a positive attitude among the study sample in their personal view of the teaching profession, reflecting their ongoing awareness of and pride in the profession, as well as their thorough preparation for it. Furthermore, the results showed statistically significant differences in the responses of the sample regarding students' attitudes towards working as teachers after graduation, attributable to the variable of academic year (third or fourth year). However, no statistically significant differences were found at the 0.05 level between the mean scores of the study sample regarding their attitudes towards working as teachers. The study examined the teaching profession after graduation, considering the variables of specialization (humanities, sciences) and geographical distance (near, far). It recommended developing incentive policies to encourage students to pursue teaching careers and improving the learning environment and academic support within educational institutions.
Keywords: Attitude, Profession, Teaching Career, University Education